ANALISA PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM TERHADAP PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2012-2021 - Andi Aprianto; Masfar Gazali (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Hotel tax is one of the regional taxes that contributes to PAD which has a fairly large contribution to PAD sources. The basis for imposing Hotel Tax is the amount paid or should be paid to the hotel. The Hotel Tax Rate is set at 10% (ten percent). The principal amount of Hotel Tax payable is calculated by multiplying the rate by the tax base. The Covid-19 pandemic has forced the government to work more in tackling the disease outbreak and its effects. The policies taken by the government will certainly have a certain impact on the community and will also have an impact on several PAD sectors which result in a decrease in revenue. Increasing local tax revenue certainly requires effectiveness and efficiency efforts. The level of efficiency is also a necessary part of increasing local tax revenues. This efficiency can be related to the expenses that will be incurred, which need to be carried out to a minimum to achieve the target of local tax revenue within a period. This study uses a quantitative descriptive analysis method with a combined panel data regression analysis between cross section and time series, with the aim of analyzing the effect of the level of effectiveness, contibution, and the level of efficiency of hotel tax revenue on the Regional Original Income of the Province of Bali in 2016 - 2020. The results show that the variables of the level of effectiveness, contribution, and hotel tax efficiency together (simultaneously) have an effect on local revenue of 98.13% and 1.87% are contributions from other variables not discussed in this study.